PPR proteins in plants: roles, mechanisms, and prospects for rice research - Meng, Lingzhi; Du, Mengxue; Zhu, Taotao; Li, Gang; Ding, Yi; Zhang, Qiang (Frontiers in Plant Science, 2024)
Pentatricopeptide repeat (PPR) proteins constitute one of the largest protein families in land plants, with over 300 members in various species. Nearly all PPR proteins are nuclear-encoded and targeted to the chloroplast and mitochondria, modulating organellar gene expression by participating in RNA metabolism, including mRNA stability, RNA editing, RNA splicing, and translation initiation. Organelle RNA metabolism significantly influences chloroplast and mitochondria functions, impacting plant photosynthesis, respiration, and environmental responses. Over the past decades, PPR proteins have emerged as a research focus in molecular biology due to their diverse roles throughout plant life. This review summarizes recent progress in understanding the roles and molecular mechanisms of PPR proteins, emphasizing their functions in fertility, abiotic and biotic stress, grain quality, and chloroplast development in rice. Furthermore, we discuss prospects for PPR family research in rice, aiming to provide a theoretical foundation for future investigations and applications.